(untitled) (Global Journal of Management and Business Research, 2013)
Risk management is a cornerstone of prudent Banking practice. Undoubtedly all Banks in the present-day volatile environment are facing a large number of risks such as credit risk, liquidity risk, foreign exchange risk, market risk and interest rate risk, among others -risks which may threaten a Bank’s survival and success. Banking is a business of risk. For this reason, efficient Risk Management is absolutely required. With a view to strengthen the Risk Management in the Banks across the Globe, Basel Frameworks have made concerted efforts to address all the issues relating to Financial Risks like Credit, Market Risk and Operational Risk and some other non-Financial Risks as well. The impact of the non-Financial Risks is all pervasive and can be severe enough that they can lead to total collapse of the Banks. This research paper briefs about the training inputs of the Banking personnel in the Credit Risk in the select sample Banks.